Solving the Coral Species Delimitation Conundrum. (20th September 2021) - Ramírez-Portilla, Catalina; Baird, Andrew H; Cowman, Peter F; Quattrini, Andrea M; Harii, Saki; Sinniger, Frederic; Flot, Jean-François
Abstract: Distinguishing coral species is not only crucial for physiological, ecological, and evolutionary studies but also to enable effective management of threatened reef ecosystems. However, traditional hypotheses that delineate coral species based on morphological traits from the coral skeleton are frequently at odds with tree-based molecular approaches. Additionally, a dearth of species-level molecular markers has made species delimitation particularly challenging in species-rich coral genera, leading to the widespread assumption that interspecific hybridization might be responsible for this apparent conundrum. Here, we used three lines of evidence—morphology, breeding trials, and molecular approaches—to identify species boundaries in a group of ecologically important tabular Acropora corals. In contrast to previous studies, our morphological analysis yielded groups that were congruent with experimental crosses as well as with coalescent-based and allele sharing-based multilocus approaches to species delimitation. Our results suggest that species of the genus Acropora are reproductively isolated and independently evolving units that can be distinguished morphologically. These findings not only pave the way for a taxonomic revision of coral species but also outline an approach that can provide a solid basis to address species delimitation and provide conservation support to a wide variety of keystone organisms. [ Acropora ; coral reefs; hybridization; reproductive isolation; taxonomy.]